Acute lung injury and recovery in patients with refractory VT/VF cardiac arrest treated with prolonged CPR and veno-arterial extracorporeal membrane oxygenation. (January 2023) - Gutierrez, Alejandra; Kalra, Rajat; Elliott, Andrea M.; Marquez, Alexandra; Yannopoulos, Demetris; Bartos, Jason A.
Abstract: Aim: Describe the lung injury patterns among patients presenting with refractory ventricular tachycardia/ventricular fibrillation out-of-hospital cardiac arrest (VT/VF OHCA) supported with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) facilitated resuscitation. Methods: In this retrospective single-center cohort study including VT/VF OHCA patients supported with VA ECMO, we compared OHCA characteristics, post-arrest computed tomography (CT) scans, ventilator parameters, and other lung-related pathology between survivors, patients who developed brain death, and those with other causes of death. Results: Among 138 patients, 48/138 (34.8%) survived, 31/138 (22.4%) developed brain death, and 59/138 (42.7%) died of other causes. Successful extubation was achieved in 39/138 (28%) with a median time to extubation of 8.0 days (6.0, 11.0) in those who survived. Tracheostomy was required in 15/48 (31.3%) survivors. Chest CT obtained on all patients showed lung injury in at least one lung area in 124/135 (91.8%) patients, predominantly in the dependent posterior areas. There was no association between the number of affected areas and survival. Lung compliance was low on admission [26 (19, 33) ml/cmH2 0], improved throughout hospitalization (p = 0.03), and recovered faster in survivors compared to those who died (p < 0.001). VA-ECMO allowed the use of lung-protective ventilation while maintaining normalized PaO2 and PaCO2 . Patients treated with V-A ECMO and either IABP or Impella had lower pulmonary compliance and more affected areas on their CT compared to those treated with V-A ECMO alone. Conclusions: Lung injury is common among patients with refractory VT/VF OHCA requiring V-A ECMO, but imaging severity is not associated with survival. Reductions in lung compliance accompany post-arrest lung injury while compliance recovery is associated with survival.